Comparison Study of Mechanical Properties of Al-Si Alloy with and without Nanoreinforce Iron Oxide (Fe2O3) - Cepi Yazirin; Poppy Puspitasari; Muhamad Fatikul Arif (Journal of Mechanical Engineering Science and Technology (JMEST), 2019)
Nanoreinforce materials such as ZnO, eggshell, Al2O3, TiO2, and ZrO2 have been shown to improve the mechanical properties of Al-Si alloy. Nanomaterial Fe2O3 has many applications as catalysts reaction in electronic devices, for example, semiconductor materials, paint formulations, lithium rechargeable batteries, and is often applied in industrial fields. It is known that Fe2O3 can be synthesized through the stirring process on machine and method used will involve several steps that relatively take a long time. In this study, Al-Si alloy reinforced by using nanomaterial Fe2O3 which sintered at a temperature of 600°C for 3 hours aimed to improve mechanical and morphological properties of Al-Si alloy. The method used was stir casting, where this method was known as flexible, simple, and economic. The result of reinforcing Al-Si alloy by using nanomaterial Fe2O3 had affected on the hardness level of Al-Si alloys as evidenced by the fracture morphology that was brittle and had a light reflection